Using field experiments to analyze changes in electronic data capture adoption decisions - Irwan Susanto (JURNAL INFOTEL, 2022)
Lacovou presented research results in a framework that describes the role of the determinants of technology, organization, and environment simultaneously influencing the innovation adoption decision-making process. The Lacovou framework is an extension study of the Tornatzky framework. Tornatzky's framework addresses three determinants that influence innovation adoption. Unfortunately, Lacovou did not present how the decision process took place. Decisions can be rational or irrational. Ajzen and several other studies defined rational decisions as decisions based on considered information or for a reason as. Previous research had not revealed empirically the rational calculation process in making innovation adoption decisions. Innovation adoption is someone's choice when he/she perceive the benefit and feel appropriate the innovation and will use or intend to use it. This study intends to reveal how the process of rational calculation in the decision-making adoption of innovations through the field experiment method. This study also reveals whether the decision of Small Medium Enterprises (SMEs) to adopt Electronic Data Capture (EDC) is rational. Research analysis using descriptive analysis method. The results show that the rational calculation process can be observed through the field experiment method. The shift in decisions represented by changes in the data on the number of subjects who make adoption decisions illustrate the rational calculation process. The results show that the decision of SMEs in adopting EDC is mostly rational. The yields of this field experiment- research was confirming Lacovou framework. The research illustrates the simulation of the effect of a combination of perceived benefits, organizational readiness, and environmental factors simultaneously